Italian Validation of the 12-Item Multiple Sclerosis Walking Scale. (26th March 2015) - Solaro, C.; Trabucco, E.; Signori, A.; Cella, M.; Messmer Uccelli, M.; Brichetto, G.; Cavalla, P.; Gironi, M.; Patti, F.; Prosperini, L.
Abstract : Objective . Gait impairment is commonly in people with multiple sclerosis (MS). The 12-item MS walking scale (MSWS-12) assesses patients' measurement of walking quality. The aim of this study was to cross-culturally adapt and validate the MSWS-12 for the Italian population with MS. Methods . Six MS out-patient clinics across Italy enrolled subjects between June 2013 and December 2013. Construct validity of MSWS-12 was determined by examining correlations with the Italian version of the EDSS, the timed 25-foot walk (T25FW), and the Fatigue Severity Scale (FSS). Results . 321 MS subjects were enrolled. Mean age was 47.55 years and mean disease duration was 13.8 years. Mean EDSS score was 4.46. 185 subjects had a relapsing-remitting course, 92 were secondary progressive, 43 were primary progressive, and 1 had a clinically isolated syndrome. The mean total score of the MSWS-12 was 49.6 (SD: 31) with values ranging between 0 and 100. Correlations between the MSWS-12 with age, disease duration, and disease course were found but not with gender. Values of the MSWS-12/IT were significantly related to EDSS (0.71), to the T25FW (0.65), and to the FSS (0.51). Conclusion . MSWS-12/IT has been adapted and validated, it is a reliable and reproducible scale for Italian patients with MS.